STUDI EVALUASI KOMPETENSI MENGAJAR MAHASISWA PRAKTEK PENGALAMAN LAPANGAN (PPL) JURUSAN AKUNTANSI UNIVERSITAS NEGERI SEMARANG - Mukhibad, Hasan; Susilowati, Nurdian (Lembaran Ilmu Kependidikan, 2010)
This research is aimed at revealing the success of the Teaching Practice Program ofstudents of Accounting of Economics Faculty of Unnes in senior high schools andvocational high school in Semarang. The samples, 49 students out of 97, wereselected through a simple random sampling. The data were collected with aquestionairre and documentation. The data were analyzed using the percentagedescriptive analysis and multiple regression analysis. The result of the study showedthat most of accounting students were successful in doing the Teaching PracticeProgram with high criteria. The success of the program was influenced by the role ofthe mentor, the role of the advising lecturer, the quality of the orientation program, therole of peers, and the achievement on the educational subjects.Kata Kunci :keberhasilan PPL, guru pamong, dosen pembimbing, orientasi PPL,rekan sejawat dan hasil belajar kependidikan